STUDENTS’ ABILITY IN USING PREPOSITION IN WRITING REPORT TEXT OF ELEVENTH GRADE OF KESAMBEN SENIOR HIGH SCHOOL (RETAIN, 2016)
STUDENTS’ ABILITY IN USING PREPOSITION IN WRITING REPORT TEXT OF ELEVENTH GRADE OF KESAMBEN SENIOR HIGH SCHOOL Siwi Purwo Kanti English Department, Languages and Arts Faculty, The State University of Surabaya Email: siwikanti@mhs.unesa.ac.id Dr. Oikurema Purwati, M.A., M.Appl. English Department, Languages and Arts Faculty, The State University of Surabaya Email: pungki_unesa@yahoo.co.id Abstract This study utilized the qualitative method to explore the students’ ability in using particular prepositions. In this study, the researcher observed the students task result to obtain the data which measure the students ability in using preposition “in”, “on”, “at” as prepositions of place and time. This study conducted in eleventh grade of senior high school. In brief, the students’ ability in using preposition “in”, “on”, “at” as preposition of place belongs to good category thought there are few students who were not able to do the task well. Meanwhile, the students seemed get quite confuse when they had to write a report text using preposition “in”, “on”, and “at” as preposition of time. Many of them could not differentiate the use of each preposition. Therefore, the students’ ability in using preposition “in”, “on”, “at” as preposition of time is in fair category. Keywords: Preposition, Preposition of Place, Preposition of Time, Students’ Ability Abstrak Penelitian ini menggunakan metode kualitatif untuk mengetahui kemampuan siswa dalam menggunakan preposisi tertentu. Dalam penelitian ini, penulis mengamati hasil kerja siswa untuk memperoleh data yang mengukur kemampuan siswa dalam menggunakan preposisi “in”, “on”, “at” sebagai preposisi tempat dan waktu. Penelitian ini dilakukan di kelas sebelas sekolah menengah atas. Pada kesimpulannya, kemampuan siswa dalam menggunakan preposisi “in”, “on”, dan “at” sebagai preposisi tempat masuk dalam kategori baik, meskipun masih ada beberapa siswa yang masih belum bisa mengerjakan tugas tersebut dengan baik. Sementara itu, siswa terlihat cukup bingung ketika harus menulis teks report menggunakan preposisi “in”, “on”, dan “at” sebagai preposisi waktu. Banyak dari mereka yang tidak bisa membedakan penggunaan preposisi. Oleh karena itu, kemampuan siswa dalam menggunakan preposisi “in”, “on”, dan “at” sebagai preposisi waktu masih dalam kategori cukup. Kata Kunci: Preposisi, Preposisi Tempat, Preposisi Waktu, Kemampuan Siswa